The Role of Mofusand as an Original and Collaborative Product in Japanese Popular Culture - Veby Aulia Ramadhani; Nisia Dwi Agusta (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2026)
This study aims to analyze the role of Mofusand as both an original product and a collaborative product in Japanese popular culture. As a popular kawaii character, Mofusand has developed not only as a visual illustration but also as a commercial product distributed across various sectors, including fashion, food, and household goods. This research employs a qualitative descriptive method with a literature study approach. The data were collected from journals, articles, official websites, and documentation related to Mofusand products. The analysis was conducted using a descriptive analytical technique to interpret the role of Mofusand in both its original products and collaborative products. The results show that Mofusand plays a significant role in expanding market reach and increasing consumer interest through its presence in various product categories. In addition, Mofusand contributes to the dissemination of kawaii culture.